Tracking the Network of Hadith Ulama in The Archipelago: Contribution of Minangkabau Ulama in 20th Century Hadith Science Education - Dairina Yusri; Itrayuni Itrayuni; Muhammad Ilham (STAI Serdang Lubuk Pakam, 2023)
Indonesia is known as the land of the archipelago which gave birth to many scholars, including in the field of hadith. Thanks to them hadith education became popular in Indonesia. In this regard, this study aims to analyze the contribution of Minangkabau scholars in Hadith Science education. The focus is on three things, namely development, biography, and contribution. The focus of the study is only on the 20th century. The research method uses library research, with the main data source being the work of these scholars in the science of hadith, secondary sources of relevant scientific works. Data collection uses the documentation method, then the content is analyzed. The results of the study revealed that the development of hadith studies in the archipelago was late in development compared to other scientific studies, the progress of its development only began in the 20th century. Scholars who are popular in the science of hadith in Minangkabau are Shaykh Yasin al-Fadani, Prof. Mahmud Yunus, and Buya Mawardi Muhammad. His contribution can be seen from his activities of collecting sanad, scientific work, incorporating hadith science into the curriculum, and spreading the science of hadith. The results of this study have implications for the basis for studying hadith scholars in other areas.